1.

(a) f ( x) = x 3 − x 2 − 14 x + 24 Factor (x + 4) 2x −1
(i ) f ( x) = ; g ( x) = x + 1
x+2
  (i) (x + 4) x3 − x 2 − 14 x + 24
2( x + 1) − 1
Through Synthetic Division fg ( x) =
  ( x + 1) + 2
 
-4 1 -1 -14 +24 2x + 2 −1
  fg ( x) =
↓ -4 20 -24 x +1+ 2
1 -5 6 0 2x +1
  fg ( x) =
Since the Remainder is Zero we can x+3
  ( c ) Given 5 3 x − 2 = 7 x + 2 Show that
conclude that ( x + 4) is a factor of f ( x).
2(log 5 + log 7)
x=
(ii )The other linear factors can be found from the (log 125 − log 7)
 
quadratic expression. 53 x − 2 = 7 x + 2
  ( x + 4)( x 2 − 5 x + 6) (3 x − 2) log 5 = ( x + 2) log 7
Factorize : ( x − 5 x + 6)
2
  3 x log 5 − 2 log 5 = x log 7 + 2 log 7  
( x − 2 x)(−3 x + 6)
2
3 x log 5 − x log 7 = 2 log 7 + 2 log 5
 
x( x − 2) − 3( x − 2) x (3 log 5 − log 7) = 2(log 7 + log 5)
  ( x − 2)( x − 3) 2(log 7 + log 5)
x=
Therefore there are 3 factors.   (3 log 5 − log 7)
( x + 4)( x − 2)( x − 3) 2(log 5 + log 7)
x=
2 x − 1 (log 125 − log 7)
(b )G iv e n f ( x ) =
x + 2
(i) In v e rse f − 1
( x )  
2 x − 1
f ( x ) =  
x + 2
2 x − 1  
y =
x + 2
2 y − 1  
x =
y + 2
 
x ( y + 2 ) = 2 y − 1
xy + 2 x = 2 y − 1  
xy − 2 y = − 1 − 2 x
 
y ( x − 2 ) = − 1 − 2 x
− 1 − 2 x  
y =
x − 2
− 1 − 2 x  
− 1
f =
x − 2
 
 
3.( a ) ( x − h) 2 + ( y − k ) 2 = r 2
2.(a) f (x) = 3x +6x −1
2

( x − 2) 2 + ( y − 1) 2 = r 2
(i) Express f (x) in the formof a (x +h) +k   2
 
Find the value of the radius (r),
  3x2 +6x −1 Note that the radius r is the  distance AB.
3(x2 +2) −1 r = ( x2 − x1 ) 2 + ( y2 − y1 ) 2
   
3(x2 +2x +12) −1−3 r = (10 − 2) + (7 − 1) 2
2

   
3(x +1) −4
2
r = 64 + 36
(ii) Therefore the minimumis k = - 4.    
r = 100
  r = 10  
(iii) The minimumvalue of x = -1. ( x − 2) + ( y − 1) = 10
2 2 2
   
2 (b) Find the values of x for which: ( x − 2)( x − 2) + ( y − 1)( y − 1) = 100
2x2 +3x −5 ≥ 0   x 2 − 4 x + 4 + y 2 − 2 y + 1 = 100
  2x2 +5x −2x −5 ≥ 0 Factorize AC Method x 2 − 4 x + y 2 − 2 y = 100 − 4 − 1
(2x2 +5x)(−2x −5) ≥ 0 x 2 − 4 x + y 2 − 2 y = 95
   
x(2x +5) −1(2x +5) ≥ 0 x 2 + y 2 − 4 x − 2 y − 95 = 0
 
(2x +5)(x −1) ≥ 0 x 2 + y 2 + hx + gy + k = 0  
(ii )Equation of line AB.
(2x +5) ≥ 0 (x −1) ≥ 0 Zero Product Theorem  
Use points given, A and B.
−5
  x≥ x ≥1 7 −1  
2 m=
  10 − 2
 
3
m = gradient of line
  4  
3
  y = x+c  
4
3
    1 = (2) + c
4
  3  
1= +c
2
   
1
c=−
  2 
3 1
  AB → y = x −
4   2
Equation of line l is perpendicular therefore;
   
3
y = − x+c
    4
4
  7 =  − (10) + c
3
  61
c=
3
3 61
∴y = − x+
4 3
5 x 2 +1 4 x 0 +1
5.(a ) y = x 3 − 3 x 2 + 2 6.( a ) ∫ 5 x + 4 dx =
2
+ +C
(i ) Stationary Points of y. 2 +1 0 +1
   
y = x3 − 3x 2 + 2 5 x3
= + 4x + C
    3
y ' = 3x 2 − 6 x = 0
π
∴ Factorizing   2  
3 x( x − 2) = 0  
(b ) ∫ 3 sin x − 5 cos xdx 
3x = 0; ( x − 2) = 0 0
π π  
x = 0; x=2 2 2
to find the y coordinates of these = 3 ∫ sin xdx − 5 ∫ cos xdx
 
stationary points. 0 0

y = (0)3 − 3(0) 2 + 2 = 3(cos x ) − 5( − sin x )
y=2 = 3 cos x + 5 sin x  
 
∴ (0, 2) ⎛ π π⎞  
= ⎜ 3 cos + 5 sin ⎟ − ( 3 cos 0 + 5 sin 0 )
y  = (2)3 − 3(2) 2 + 2 ⎝ 2 2⎠  
y = (2, −2) = ( 3(0) + 5(1) ) − ( 3(1) + 5(0)
 
  )
To determine the nature of the points.
  = (5) − (3)  
we find the second derivative and test:
  =2
y '' = 6 x − 6  
= 6(0)
  −6
 
=-6  
since -6 ≤ 0 we can conclude its a maximum.  
 
y '' = 6 x − 6  
= 6(2) − 6  
 
=  6;
 
since 6 ≥ 0 we can conclude its a minimum.
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
3. (b)   (c) 

   

   

   

   

   

   

   

    

   
Given vectors
Given that they are prependicular    
OA = −2i + 5 j
then we know that the dot product is Zero.  
  OB = 3i − 7 j
Dot Product
AB = AO + OB note the change in direction
a · b = a × b × cos (θ )  
  of vector OA .
a · b = a × b × cos ( 90°)   = 2i − 5 j + 3i − 7 j
 
a · b= a × b × 0   = 5i − 12 j
a · b= 0 Now we find the magnitude of the resultant vector.
 
∴a · b = a x × bx + a y × by AB = 52 + (12) 2
 
 
0 = 10 × λ + −8×10 AB = 25 + 144
 
AB = 169
  0 = 10λ − 80
AB = 13 square root of 169.  
  −10λ = −80
∴ the unit vector in the direction of AB.
  λ =8
  1
( 5i − 12 j )
  13
 

   

   

   

   
 
θ
4(a ) Areea of sec torr = ×π r2
 
360
1 2
or = rθ  
2
we needd to find the radius "r".  
we are given the peerimeter, thatt is, the arc lenght
l plus
 
the radiius twice.
Recall that:
t  
Arc lennght = rθ , whhere θ is in radians.
r
 
5
∴ rθ + r + r = (122 + π )
6  
5
rθ + 2r = (12 +  π )
6
  5  
r (θ + 2) = (12 + π ) Factorizze, r.
dy 6
6(cc) Given thaat = 2 - 2 x is the derivaative
   
dx 5
(12 + π )
theen integratinng would givve us the     r= 6
funnction of thee curve. θ +2
    5
∫ 2 − 2 x dx (12 + π )
6 π
    r = , note θ =
= 2x − x2 + C π 6
+2
= 2x − x2 + 8     6
r=5
C = 8; since C is the y inteercept, (0,8).
  1 2  
wee integrate too find the areea under curvve. Area off sector = rθ
4
2
π π
∫ 2x − x + 8 dx 1
2
  Area = 52 * using θ = .
0 2 6 6  
2 x 2 x3   1
= − + 8x Area = × π  25
2 3   12
valuate from 0 to 4.
Ev 25π   2
Area = units
  12
⎛ 2(4) 2 (4)3 ⎞ ⎛ 2(0) 2 (0)3 ⎞
=⎜ − + 8(4) ⎟ − ⎜ − + 8(0) ⎟  
⎝ 2 3 ⎠ ⎝ 2 3   ⎠
64  
= 48 − + 32 − 0  
3  
2  
= 26 unitts 2 would bee the Area unnder the curvve.
3  
 

 
4(c) Compound Angle Formula for
 
tan A ± tan B
tan( A ± B ) =
 
1 ∓ tan A tan B
1  
Given tan(θ − α ) =
  2
tan θ − tan α
tan(θ − α ) =
1 + tan θ tan α
tan θ − tan α 1
=
1 + tan θ tan α 2
3 − tan α 1
= ; note that tan θ = 3
1 + 3 tan α 2
2 ( 3 − tan α ) = 1(1 + 3 tan α )
6 − 2 tan α = 1 + 3 tan α
−2 tan α − 3 tan α = 1 − 6
− 5 tan α = −5
−5
tan α =
−5
tan α = 1
α = tan −1 (1)
α = 45